Penerapan Model Project Based Learning dalam Pembelajaran Menulis Teks Laporan Hasil Observasi Kelas VIII SMP Negeri 17 Kota Jambi - Maizarra, Deva; Rustam, Rustam; Yusra, Himan (Jurnal Ilmiah Dikdaya, 2024)
The purpose of this research is to determine the application of the project based learning model in learning to writereport texts based on observations of class VIII students at SMP Negeri 17 Jambi City. The approach in this research uses aqualitative approach with a descriptive research approach. Data collection was carried out by means of interviews, observationsand documentation in the field. The results of this research show the application of project based learning, where students areable to solve a problem through project assignments carried out in groups, through this students are able to exchange ideas withetheir colleagues in solving a problem. It can be concluded that the implementation of project based learning has gone wellaccording to the PJBL steps.